Forest structure, diversity and regeneration potential along altitudinal gradient in Dhanaulti of Garhwal Himalaya - Sushil Saha; Govind-Singh Rajwar; Munesh Kumar (Forest Systems, 2016)
Aim of the study: The aim of the present study was to understatnd the forest composition, structure, diversity and regeneration potential along altitudinal gradient.